Gothic Implications on the Enlightenment, Puritanism, and Transcendentalism in Charles Brockden Brown's Wieland - Gayret, Gökçenaz (Muş Alparslan Üniversitesi, 2020)
The impetus behind the current study lies in exploring how Charles Brockden Brown expostulates reason and rationalism by posing questions to Enlightenment ideas, criticizes Puritanism through addressing the detrimental influence of religious fanaticism on society and humanity, and violates Transcendentalist concept of the inherently good and dignified human with gothic representations in Wieland. Brown underlines the dark applications of reason, obsessive religious melancholy, and destructive evil nature of humanity by locating the sources of terror and retaining a gothic mood of emotional and psychological extremity in the novel. The study shows that Brown violates the idea that reason ensures the progress of humanity; offers his critiques of the impending influence of religious mania on humanity by addressing Puritanism; and questions the transcendentalist view by presenting how the perverse nature of evil buried within each individual drags humans into diabolical actions through gothic elements which do not deal with rationality.

Bu çalışma, Charles Brockden Brown’un Wieland adlı eserinde gotik betimlemelerle Aydınlanma fikirlerine sorular yönelterek akıl ve rasyonelliğe nasıl karşı çıktığını, toplum ve insanlık üzerinde köktendinciliğin zarar verici etkisine göndermede bulunarak Püritanizmi nasıl eleştirdiğini ve insanı doğası gereği iyi ve saygın kılan Transandantal düşünceyi nasıl çiğnediğini incelemeyi amaçlamaktadır. Eserde, Brown korku kaynaklarını saptayarak ve duygusal ve ruhsal aşırıcılığın gotik mizacını sürdürerek aklın kötüye kullanılmasının, saplantılı dini melankolinin ve insanlığın habis doğasının altını çizmektedir. Çalışma, Brown’un rasyonellikle ile özdeşleşmeyen gotik elementler ile aklın insanlığın ilerlemesini temin ettiğini savunan düşünceyi tanımadığını, Püritanizme göndermelerde bulunarak insanlık üzerinde dini tutuculuğun yıkıcı etkilerine, dair eleştiriler sunduğunu, bireyin kötü doğasının insanlığı nasıl şeytani eylemlere sürüklediğini göstererek transandantal görüşü sorguladığını göstermektedir.
Charles Brockden Brown’un Wieland Adlı Eserinde Aydınlanma, Püritanizm ve Transandantalizm Üzerine Gotik Çıkarımlar
anemon
Keywords: Gothic; The Enlightenment; Transcendentalism; Reason; Rationality; Gotik; Aydınlanma; Transandantalizm; Akıl; Rasyonellik